SUN-LB45 Identifying a Role for Lactogenic Hormones in Maternal Motivation - Swart, Judith M (J Endocr Soc, 2020)
The onset of appropriate maternal behaviour is essential for the survival of dependent offspring in mammals. Lactogenic hormones, including prolactin and placental lactogen, play an important role in the regulation of this behaviour, mediated through prolactin receptor expression in the medial preoptic area (MPOA) of the hypothalamus(1). However, it is unclear how lactogenic action in this region induces the display of maternal behaviour. It has been shown that activation of neuronal projections from the MPOA to the ventral tegmental area (VTA) is necessary for maternal behaviour(2), with reward circuitry activated in order to motivate a mother to invest in time- and resource-costly care for her young. We aimed to investigate whether lactogenic hormones play a role in the activation of reward circuitry for maternal behaviour. First, we characterised specific aspects of motivation and reward behaviour in wildtype female C57BL/6 mice of different reproductive states, using three behavioural testing paradigms. We showed that virgin and pregnant mice develop a preference for contexts associated with the presence of foster pups in a conditioned place preference test (p<0.01, n=9 per group), an aspect of reward behaviour that was not observed in lactating females (p=0.14, n=8). However, in a novel T maze and when a climbable barrier was placed in the home cage, virgin and pregnant mice showed low motivation for pup retrieval compared to lactating mice (p<0.05, n≤6 per group). These data demonstrate that reproductive state differentially affects passive reward learning and active motivation for maternal care in wildtype mice. Moreover, we can differentiate between maternal and non-maternal states of pup-related reward behaviour with the use of the T maze and barrier climbing paradigms. Next, we tested mice with a conditional deletion of prolactin receptors in Gamma-Aminobutyric Acid (GABA) neurons (Prlr flox/VGat Cre) in the T maze during lactation. Knockout mice showed incomplete retrieval behaviour, and latencies for pup retrieval were significantly longer than in controls (p<0.01, n≤6 per group). The behavioural impairments observed in Prlr flox/VGat Cre knockout mice in the T maze imply that the action of lactogenic hormones on GABA neurons is required for full maternal motivation. 1.Brown RSE, et al. Prolactin action in the medial preoptic area is necessary for postpartum maternal nursing behavior. Proc Natl Acad Sci U S A114, 10779-10784 (2017). 2.Fang YY, Yamaguchi T, Song SC, Tritsch NX, Lin D. A Hypothalamic Midbrain Pathway Essential for Driving Maternal Behaviors. Neuron98, 192-207 e110 (2018).